A vontade de verdade em José Saramago - Assunção, Karina Luiza de Freitas (2015)
The general aim of this paper is to problematize the formation of truth in the novels Acaverna (2000), O HomemDuplicado (2008), Memorial Do Convento (2008a) and OEvangelho Segundo Jesus Cristo (1997) for the purpose of understand the truth willingness and truth games functioning in these literary works. From that general objective, we have elected the following specific objectives: to point how history, truth willingness and truth policies , from the foucauldian bias contribute to the comprehension of discourses form; problematize the relationship between Discourse Analysis and the truth concept to show the usefulness of this concept to this subject; and analyze the truth formation in the saramaguiano novels, paying attention to headings which point to religious, historical and common sense themes, that emerge from the literary works selected to this research corpus. To the paper purpose development, based on the assumption that these discourses which permeate these novels production circumscribe itself to historical production conditions, that determinate discursive regularities which allow the truth willingness re-elaboration , and consequently, the truth games present in these mentioned literary works. From that assumption, we defend the thesis of the questioning of crystallized truth realized in the analyzed literary works emerges through an inversion in the narratives, since the certainties of common sense, historical and biblical discourses become fiction and what would be in the margins of these truths emerges aiming to point the fragility, changing and contradiction that last through both the subjects formation and its discourses.Thus, we conclude that the comprehension of the truth discursive functioning is essential to the Discourse Analysis, because it helped to show that when a given discourse is presented as true, we should pay attention to its emergence rules and consider it as relative, since we can question it and identify its formation rules, and consequently, it can lose its truth place. Besides, we have observed that the willingness truth which emerges from the analyzed literary works does not come to show another truth that replaces the first, but to test the constitutive contradiction of characters, and consequently, of discourses. Therefore, the willingness truth which forms part of saramaguiano literary works does not point to a centered truth, but for a future to be built by the characters.